EFFECT OF ETRACCTION PROCEDURE ON THE INHIBITION OF SANTONICA PLANT AGAINST SPECTRUM OF ISOLATED BACTERIA - Yaseen, Ali Ameen (Diyala Agricultural Sciences Journal, 2010)
The study showed that the Santonica (Artemisia herbaalba) plant had considerable inhabitation activity against some of positive gram and negative isolated bacteria. Ethyl acetate, Ethanol ٨٠٪ and Hexan as well as the distal water were used as solvents to the active materials in this plant. The aim of this study was identify the ability of these solvents to extract the active materials in this plant which had effect the inhabitation ability against these bacteria by using the disc division procedure. The study showed that the extraction procedure followed had clear effect on inhabitation ability of Santonica against these bacteria. In time that the supported paper disc with the alcohol extraction from plant to compose a clear zone of diameter ١١. ٤٥ and ٧ and ٦٫٥٥ mm. When positioned in plates were seeded by white Staphylococcus aureus, Pseudomonas aeruginosa and Bacillus cereus respectively. While this disc failed in occurring any inhabitation for the same bacteria when it saturated by aqueous extraction for the same plant. Also the study has showed that the ethyl acetate extract for Santonica succeeded in occurring clear inhabitation against the tested bacteria, the clear zone diameter which supported by ethyl acetate was ١١, ١٢, ١٢, ١١٫٧٦ and ١٢ mm. When positioned in plates were seeded with white Staphylococcus aureus ,Pseudomonas aeruginosa , Bacillus cereus , golden Staphylococcus aureus and Salmonella typhimurium respectively , while the E. coli has showed ability to resist this extraction. The hexane extractions of the same plant didn´t show any clear effect against the tested bacteria, except for E. coli and golden Staphylococcus aureus.